Study on Crop Diversification & Diversified Farming System - Benaka Prasad SB, Humeera Tazeen (International Journal of Modern Agriculture, 2021)
Crop diversification is among the most pocket friendly means of reducing farmers’ income uncertainties, especially for poor small farmers. Poverty, however, is a nuanced term that requires more than just money. This analysis looks at the influence of the divergence of crops to Sustainable Development Goals, while also taking account of other dimensions of poverty: food safety, nutrition and climate change vulnerability. Indian rural economies are essentially known as crop economies. The diversification level of agricultural enterprises represents the degree of economic growth in rural areas. Agriculture is faced with the omnipresent issue of decision-making on the profitable diversification of crop production. The crop diversification has been largely seen as a ray of hope for their economic development for the rural economy as a whole, and particularly for small and marginal farmers. Agricultural diversification is often practiced to avoid risks and uncertainties that indicate climate and organic vagaries. The farmers in general grow their livelihoods at the early stage of growth. As the population increases, they are trying to grow more so that overall output in the farm is maximized.